CEO POVERTY EXPERIENCE AND CORPORATE SOCIAL RESPONSIBILITY: ANALYSIS IN COVID-19 PERIOD FOR ENVIRONMENTALLY SENSITIVE INDUSTRIES - Rahayuningsih, Deasy Ariyanti; Rudyanto, Astrid; Sintya, Sherina (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
The Indonesian government pursues sustainable development goals with CSR from organizations. Sustainable development goals begin with ending global poverty. As Indonesia still suffers from poverty (especially during COVID 19), it is imperative to analyze the effect of CEO poverty experience on CSR in COVID 19 period. 207 Indonesia Stock Exchange-listed environmentally sensitive enterprises from 2020-2022 were sampled for this report. This analysis demonstrates that CEO poverty has negative effect on CSR using Driscoll-kraay standard errors. The difference between this finding and previous research (which is done in China) is in the moral of poor people. While China’s poor people has positive perspective of poverty, Indonesia holds the opposite view. The implication of this study is government need to fix the moral of Indonesian people, especially the poor ones.